Lessons we have learned from the myth of the phoenix: The eternal return (Orfeu, 2021)
In this essay I write about the changes that occurred in the world in different eras in the field of Education and, for understanding this phenomenon, we adopt the conception of mythic time, as suggested by Mircea Eliade, who see in the occidental society, prominently inserted in a linear time, many examples of what he calls “eternal return”, which means the cyclic return, in subsequent times, of occurrences that already occurred As a metaphor of this idea, I bring the figure of the phoenix, due to its eternal rebirth ability. I intend to examine some procedures in music education, as they appear in different moments in history, as examples of the coming back of old conceptions in Education and Music Education that have already occurred in different places, at different times. At the end, I show some current education procedures that are inserted in two fronts, one is predominantly technical, and the other is primarily focused on the human being, according to a certain individual and social reality. Among these educators I highlight those who provided creative answers in their classes to the actual problem faced by all of us around the world. Their musical interventions were considered answers to the questions they had to deal with also point out that many of the analyzed procedures are similar to educational proposals already seen in prior times. Accordingly, it is difficult to say what is really new and what is definitely old.
Keywords: Music Education; Eternal Return; Historical Revision; Nowadays Proposals